PENDEKATAN HERMENEUTIC DAN TEOLOGIS STUDI ISLAM PADA ANAK - Ade Chayawyta; Eva Fajar S; Marlia Sholikhah; Muhammad Baharuddin R.L. (STPI Bina Insan Mulia Yogyakarta, 2019)
This paper seeks to present an interpretation with a theological and hermeneutical approach to Islamic studies for children. Where Islamic studies are now no longer confined to the area of ​​jurisprudence, kalam, Sufism and philosophy, but also began to come into contact with various perspectives and methodologies in various scientific fields such as social sciences and approach sciences, such as the hermeneutic and theological approach which is one scientific approach methodology born from the western world. With different characteristics and history, there will be differences, pros and cons of the results of these two approaches. Islamic studies of children are now also a very interesting concern. Because in the current era of globalization there is a need for studies of children, especially religious studies (Islam). Where religion becomes the basic control and education for children. Religious education plays an important role in forming good character and personality for children. Seeing from Islamic studies will be examined according to the hermeneutic approach and theological approach, so that new ideas will emerge that remain in control, namely religion. The method in this study is literature review, where information and data are collected from various sources such as books and journals. The result of the discussion is that the hermeneutic and theological approach to Islamic studies in children is an effort to understand texts, writers, and readers. These three elements form hermeneutical meaning networks. The hermeneutic reading model seeks to find the objective meaning of the text. Objectivity is not interpreted as positivism, which states that what we understand is a mirror of actual reality. Hermeneutics as a science becomes a method or way to interpret symbols in the form of text or something needed as text to find meaning and meaning, where this hermeneutic method requires the ability to interpret the past that is not experienced, then brought to the present. While the theological approach understands religion which emphasizes the formal form of religious symbols, claims to be the most true religion, others are wrong so that the views of others are false, infidel, heretical, and apostate. The normative theological approach in understanding religion literally can be interpreted as an effort to understand religion by using a framework of divinity which departs from a belief that the empirical form of religion is regarded as the most correct compared to the others.